Comparative evaluation of change propagation approaches towards resilient software evolution - Ibrahim, Noraini; Wan Kadir, Wan Mohd. Nasir; Deris, Safaai (2008)
Producing software that is adaptable to the rapid environmental changes and the dynamic nature of the business life-cycle is extensively becoming a topical issue in the software evolution. In this context, change propagation (CP) process is one of the critical parts in the software change management. Traditional strategies have projected more complex ways, resulting to substantial failures and risks. This paper presents an investigation and highlights on the desired criteria to provide better means to simplify the complicated CP tasks. The evaluation results may be used as a foundation in improving CP approaches that provide significant challenges in software evolution.